Fusarium: more than a node or a foot-shaped basal cell - Crous, P W; Lombard, L; Sandoval-Denis, M; Seifert, K A; Schroers, H-J; Chaverri, P; Gené, J; Guarro, J; Hirooka, Y; Bensch, K; Kema, G H J; Lamprecht, S C; et al. (Studies in mycology, 2021)
Recent publications have argued that there are potentially serious consequences for researchers in recognising distinct genera in the terminal fusarioid clade of the family Nectriaceae. Thus, an alternate hypothesis, namely a very broad concept of the genus Fusarium was proposed. In doing so, however, a significant body of data that supports distinct genera in Nectriaceae based on morphology, biology, and phylogeny is disregarded. A DNA phylogeny based on 19 orthologous protein-coding genes was presented to support a very broad concept of Fusarium at the F1 node in Nectriaceae. Here, we demonstrate that re-analyses of this dataset show that all 19 genes support the F3 node that represents Fusarium sensu stricto as defined by F. sambucinum (sexual morph synonym Gibberella pulicaris). The backbone of the phylogeny is resolved by the concatenated alignment, but only six of the 19 genes fully support the F1 node, representing the broad circumscription of Fusarium. Furthermore, a re-analysis of the concatenated dataset revealed alternate topologies in different phylogenetic algorithms, highlighting the deep divergence and unresolved placement of various Nectriaceae lineages proposed as members of Fusarium. Species of Fusarium s. str. are characterised by Gibberella sexual morphs, asexual morphs with thin- or thick-walled macroconidia that have variously shaped apical and basal cells, and trichothecene mycotoxin production, which separates them from other fusarioid genera. Here we show that the Wollenweber concept of Fusarium presently accounts for 20 segregate genera with clear-cut synapomorphic traits, and that fusarioid macroconidia represent a character that has been gained or lost multiple times throughout Nectriaceae. Thus, the very broad circumscription of Fusarium is blurry and without apparent synapomorphies, and does not include all genera with fusarium-like macroconidia, which are spread throughout Nectriaceae (e.g., Cosmosporella, Macroconia, Microcera). In this study four new genera are introduced, along with 18 new species and 16 new combinations. These names convey information about relationships, morphology, and ecological preference that would otherwise be lost in a broader definition of Fusarium. To assist users to correctly identify fusarioid genera and species, we introduce a new online identification database, Fusarioid-ID, accessible at www.fusarium.org. The database comprises partial sequences from multiple genes commonly used to identify fusarioid taxa (act1, CaM, his3, rpb1, rpb2, tef1, tub2, ITS, and LSU). In this paper, we also present a nomenclator of names that have been introduced in Fusarium up to January 2021 as well as their current status, types, and diagnostic DNA barcode data. In this study, researchers from 46 countries, representing taxonomists, plant pathologists, medical mycologists, quarantine officials, regulatory agencies, and students, strongly support the application and use of a more precisely delimited Fusarium (= Gibberella) concept to accommodate taxa from the robust monophyletic node F3 on the basis of a well-defined and unique combination of morphological and biochemical features. This F3 node includes, among others, species of the F. fujikuroi, F. incarnatum-equiseti, F. oxysporum, and F. sambucinum species complexes, but not species of Bisifusarium [F. dimerum species complex (SC)], Cyanonectria (F. buxicola SC), Geejayessia (F. staphyleae SC), Neocosmospora (F. solani SC) or Rectifusarium (F. ventricosum SC). The present study represents the first step to generating a new online monograph of Fusarium and allied fusarioid genera (www.fusarium.org).
Keywords: Fusisporium pandani Corda; Mycotoxins; Sporotrichum poae Peck.; Fusarium tumidum var. humi Reinking; Macroconia phlogioides Sand.-Den. & Crous; Fusarium trichothecioides Wollenw.; Fusarium pusillum Wollenw.; Fusisporium culmorum Wm.G. Sm.; Fusarium cactacearum Pasin. & Buzz.-Trav.; Fusarium ustilaginis Kellerm. & Swingle; Cephalosporium sacchari E.J. Butler; Fusarium citrinum Wollenw.; Fusarium rubiginosum Appel & Wollenw.; Selenosporium equiseti Corda; Fusarium werrikimbe J.L. Walsh, L.W. Burgess, E.C.Y. Liew & B.A. Summerell; Apiognomonia platani (Lév.) L. Lombard; Fusarium oxysporum var. asclerotium Sherb.; Fusisporium hordei Wm.G. Sm.; Fusarium longipes Wollenw. & Reinking; Fusarium sublunatum Reinking; Fusarium putrefaciens Osterw.; Novel taxa; Fusarium caudatum Wollenw.; Fusarium amentorum Lacroix; Fusarium asparagi Delacr.; Fusicolla quarantenae J.D.P. Bezerra, Sand.-Den., Crous & Souza-Motta; Neocosmospora pseudopisi Sand.-Den. & L. Lombard; Fusarium palczewskii Jacz.; Selenosporium hippocastani Corda; Fusarium idahoanum O.A. Pratt; Fusarium batatas Wollenw.; Neocosmospora tuaranensis (T. Aoki et al.) L. Lombard & Sand.-Den.; Dialonectria volutella (Ellis & Everh.) L. Lombard & Sand.-Den.; Fusarium aleyrodis Petch; Neocosmospora merkxiana Quaedvl. & Sand.-Den.; Scolecofusarium ciliatum (Link) L. Lombard, Sand.-Den. & Crous; Fusarium juruanum Henn.; Fusisporium arundinis Corda; Fusarium stillatum De Not. ex Sacc.; Fusarium heterosporioides Fautrey; Fusarium arthrosporioides Sherb.; Hymenella aurea (Corda) L. Lombard; Fusisporium avenaceum Fr.; Fusisporium elasticae Thüm.; Multi-gene phylogeny; Fusarium nigrum O.A. Pratt; Fusarium buharicum Jacz. ex Babajan & Teterevn.-Babajan; Neocosmospora obliquiseptata (T. Aoki et al.) L. Lombard & Sand.-Den.; Fusarium rhizochromatistes Sideris; Fusarium delacroixii Sacc.; Fusarium succisae Schröt. ex Sacc.; Fusarium tritici Liebman; Menispora penicillata Harz; Stylonectria corniculata Gräfenhan, Crous & Sand.-Den.; Fusisporium didymum Harting; Fusarium zygopetali Delacr.; Fusarium tabacivorum Delacr.; Fusarium prieskaense G.J. Marais & Sand.-Den.; Fusisporium flavidum Bonord.; Neocosmospora epipeda Quaedvl. & Sand.-Den.; Fusarium citriforme Jamal.; Fusarium fissum Peyl; Fusarium coccinellum Kalchbr.; Fusarium willkommii Lindau; Neocosmospora floridana (T. Aoki et al.) L. Lombard & Sand.-Den.; Setofusarium setosum (Samuels & Nirenberg) Sand.-Den. & Crous.; Fusisporium clypeaster Corda; Fusarium citrulli Taubenh.; Fusarium samoense Gehrm.; Fusarium spinaciae Hungerf.; Nothofusarium Crous, Sand.-Den. & L. Lombard; Selenosporium sarcochroum Desm; Fusisporium anthophilum A. Braun; Fusarium scirpi Lambotte & Fautrey; Fusarium eucheliae Sartory, R. Sartory & J. Mey.; Fusarium lyarnte J.L. Walsh, Sangal., L.W. Burgess, E.C.Y. Liew & Summerell; Fusarium xylarioides Steyaert; Fusarium roesleri Thüm.; Taxonomy; Fusarium albidoviolaceum Dasz.; Fusarium stilboides Wollenw.; Fusisporium lolii Wm.G. Sm.; Cosmosporella cavisperma (Corda) Sand.-Den., L. Lombard & Crous; Fusarium prunorum McAlpine; Fusarium rhodellum McAlpine; Nectriaceae; Fusarium armeniacum (G.A. Forbes et al.) L.W. Burgess & Summerell; Fusarium lateritium Nees; Luteonectria albida (Rossman) Sand.-Den. & L. Lombard; Fusarium palustre W.H. Elmer & Marra; Neocosmospora rekana (Lynn & Marinc.) L. Lombard & Sand.-Den.; Fusisporium andropogonis Cooke ex Thüm.; Setofusarium (Nirenberg & Samuels) Crous & Sand.-Den.; Fusarium martii f. phaseoli Burkh.; Fusarium cacti-maxonii Pasin. & Buzz.-Trav.; Fusisporium incarnatum Roberge ex Desm.; Fusarium rhizophilum Corda; Neocosmospora; Fusarium echinatum Sand.-Den. & G.J. Marais; Gibberella phyllostachydicola W. Yamam.